The Physician's Guide to Investing A Practical Approach to Building Wealth - Doroghazi, Robert. (Humana Press, 2009)
In comments that were unfortunately prescient, Dr. Doroghazi said in the first edition "the author feels we are currently experiencing a real estate bubble." And in anticipation of the credit crisis, he said "banks are far too lenient in their lending practices...the problem is that bankers are often not lending their own money&considering that a significant percentages of mortgages are sold to Fannie Mae (FNM) and Freddie Mac (FRE), the problem is now actually everyones." This new and expanded edition provides commonsense advice that all investors, physicians and non-physicians will find profitable in these difficult times. Learn about the power of thrift, the magnificence of compound interest, the malevolence of debt and the perniciousness of fees. See how to pay off the mortgage by age 45, fund your childrens education and retire at a reasonable age rather than continue to work because you must. This book is unique, providing advice you will find nowhere else, such as how to deal with bankers and real estate agents on your terms rather than theirs, how to save one-quarter or more on restaurant bills, the importance of charity, and why lack of financial instruction is the greatest deficiency of medical education in the United States. Dr. Doroghazi was a successful physician and is a successful investor. He paid his own way through college and medical school, graduating with Honors from the University of Chicago, Pritzker School of Medicine, and was elected to Alpha Omega Alpha. He completed his training in Internal Medicine at the Massachusetts General Hospital and Cardiology at Barnes Hospital. After retiring at age 54, he writes The Physician Investor Newsletter and is active in many charitable and civic organizations.